Anisotropic Wetting of Water on Patterned Asymmetric Nanostructure Arrays. Issue 12 (13th April 2017) - Ge, Peng; Wang, Shuli; Liu, Wendong; Wang, Tieqiang; Yu, Nianzuo; Xue, Peihong; Chen, Hongxu; Shen, Huaizhong; Zhang, Junhu; Yang, Bai
Abstract : This paper reports the directional wetting behavior of water on a patterned heterogeneous surface, which is integrated by two asymmetric nanostructures with different directions. The asymmetric nanostructures are Janus silicon cylinder arrays (Si‐CAs) modified by molecules with distinct surface energies on two sides. Through a photolithography process, the two asymmetric nanostructures are integrated in a single surface to form chessboard patterns with different directions. When water is injected onto the patterned surface, water droplets wet in a unidirectional manner, and the wetting direction is along resultant direction of the two wetting directions of water on the two asymmetric patterns. This paper investigates the factors which may influence the wetting behavior of water on the surface, experimental results show that patterned asymmetric surfaces prepared from different chessboard pattern size, Si‐CAs with different diameters, and different morphology‐symmetric structures do not affect the wetting property, but the molecules modified on two sides do. Larger surface energy difference between the modified molecules improves the ability of the surfaces induce water moving. It is believed that the patterned asymmetric nanostructure arrays provide a new strategy to modulate the wetting behavior of water, which will show potential applications in microfluidics and others involving unidirectional liquid manipulation. Abstract : Two asymmetric nanostructures arrays with different directions are integrated in a single surface. Water shows unidirectional wetting on it toward resultant direction of the two wetting directions, which provides a strategy to modulate the wetting behavior of water.